2016
DOI: 10.1038/srep23579
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Defined Populations of Differentiated Human Neural Stem Cell Progeny

Abstract: Many neurological injuries are likely too extensive for the limited repair capacity of endogenous neural stem cells (NSCs). An alternative is to isolate NSCs from a donor, and expand them in vitro as transplantation material. Numerous groups have already transplanted neural stem and precursor cells. A caveat to this approach is the undefined phenotypic distribution of the donor cells, which has three principle drawbacks: (1) Stem-like cells retain the capacity to proliferate in vivo. (2) There is little contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 60 publications
0
27
0
Order By: Relevance
“…A recent study demonstrated that exposure to different levels of purmorphamine can produce nearly pure yields of glutamatergic, GABAergic, or medium spiny neurons ( Yuan et al, 2015 ). Having precise control over the terminal phenotype of grafted cells bypasses concerns of unintended integration of other subtypes and can balance excitatory and inhibitory neuronal network activity in the recipient ( Cunningham et al, 2014 ; Fortin et al, 2016 ; Hunt et al, 2013 ). Therefore it was surprising that only 30–40% of the neurons generated in the direct differentiation protocol were GABAergic, using a concentration of SMAD inhibitors and purmorphamine that in other similar protocols yielded cultures in which 80–90% of the neurons were GABAergic ( Liu et al, 2013a ; Nicholas et al, 2013 ; Yuan et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that exposure to different levels of purmorphamine can produce nearly pure yields of glutamatergic, GABAergic, or medium spiny neurons ( Yuan et al, 2015 ). Having precise control over the terminal phenotype of grafted cells bypasses concerns of unintended integration of other subtypes and can balance excitatory and inhibitory neuronal network activity in the recipient ( Cunningham et al, 2014 ; Fortin et al, 2016 ; Hunt et al, 2013 ). Therefore it was surprising that only 30–40% of the neurons generated in the direct differentiation protocol were GABAergic, using a concentration of SMAD inhibitors and purmorphamine that in other similar protocols yielded cultures in which 80–90% of the neurons were GABAergic ( Liu et al, 2013a ; Nicholas et al, 2013 ; Yuan et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is crucial to develop new therapeutic interventions focused on restoring these lost neural populations. Recently, transplantation of human neural stem cells (NSCs) has been proposed as a promising therapy for NDs . NSCs are multipotent cells present in developing and adult brains which can differentiate into astrocytes, neurons, and oligodendrocytes .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, transplantation of human neural stem cells (NSCs) has been proposed as a promising therapy for NDs. 5 NSCs are multipotent cells present in developing and adult brains which can differentiate into astrocytes, neurons, and oligodendrocytes. 6 In the adult brain, NSCs reside in neurogenic niches, such as the subventricular zone (SVZ) and subgranular zone (SGZ), in the dentate gyrus of the hippocampus.…”
Section: Introductionmentioning
confidence: 99%
“…These additives provide support to cells during the hypothermic intervals of freezing and thawing, which dampens the induction of CIDOCD compared to traditional freezing media ( Mathew et al, 1999 ; Baust et al, 2000, 2002 ). Several studies have reported improvements in cell viability, long-term survival and cell performance after use of CryoStor for the preservation of primary human immune and stem cells, neural progenitor cells, and iPSC-derived neurons ( Stylianou et al, 2006 ; Clarke et al, 2009 ; Fortin et al, 2016 ; Seay et al, 2017 ; Wakeman et al, 2017 ). Our work provides the first application of CryoStor to primary rodent neuron cryopreservation, imparting an important new tool to neurobiology laboratories.…”
Section: Discussionmentioning
confidence: 99%